2015
DOI: 10.1021/jacs.5b06444
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Grain Morphology of Perovskite Absorber Film by Molecular Self-Assembly toward Efficient Solar Cell Exceeding 17%

Abstract: The highly developed crystallization process with respect to perovskite thin films is favorable for efficient solar cells. Here, an innovative intermolecular self-assembly approach was employed to retard the crystallization of PbI2 in dimethylformamide (DMF) by additional solvent of dimethyl sulfoxide (DMSO), which was proved to be capable of coordinating with PbI2 by coordinate covalent bond. The obtained PbI2(DMSO)x (0 ≤ x ≤ 1.86) complexes tend to be closely packed by means of intermolecular self-assembly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
302
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 367 publications
(321 citation statements)
references
References 36 publications
17
302
2
Order By: Relevance
“…It is worth noting that in this section, the photovoltaic performance of M-PSCs has been improved a lot through optimizing the deposition of CH 3 NH 3 PbI 3 by DMSO-assistant "two-step" route as reported previously (Fig. S1, Supplementary information) [35] higher PCE is selected for comparison with conventional TiO 2 underlayer with an optimized thickness of~60 nm. Table 3 shows the average photovoltaic parameters obtained from 60-70 devices for each group of M-PSCs.…”
Section: Resultsmentioning
confidence: 97%
“…It is worth noting that in this section, the photovoltaic performance of M-PSCs has been improved a lot through optimizing the deposition of CH 3 NH 3 PbI 3 by DMSO-assistant "two-step" route as reported previously (Fig. S1, Supplementary information) [35] higher PCE is selected for comparison with conventional TiO 2 underlayer with an optimized thickness of~60 nm. Table 3 shows the average photovoltaic parameters obtained from 60-70 devices for each group of M-PSCs.…”
Section: Resultsmentioning
confidence: 97%
“…This mechanism could help us to understand the impact of intermediate phases on perovskite crystal growth. Namely, the crystallinity of intermediate phases is a crucial parameter on perovskite films [26,27]. The diffraction peak intensity of the MAI-PbI2-DMSO is much higher than that of MAI-PbI2-DMF intermediate phases.…”
Section: Resultsmentioning
confidence: 99%
“…[34] Previously, it has been reported that DMSO solvent has a tendency to form an adduct with lead iodide and while employing such adducts, the fabrication of high-efficiency solar cells was reported. [12,35,36,37,38] Under standard illumination, devices based on CH(NH 2 ) 2 PbBr 3 films prepared when a single solvent (DMF) was used for the deposition of PbBr 2 , yielded a V OC of 1140 mV, ( [ 34] SEM analysis reveals the formation of elongated CH(NH 2 ) 2 PbBr 3 structures (Figure 5a) from PbBr 2 (DMF) solution, whereas smooth and uniform CH(NH 2 ) 2 PbBr 3 films ( Figure 5b) were obtained from PbBr 2 (DMF+DMSO) solution. We further evaluated the role of solvent on the emission characteristics of CH(NH 2 ) 2 PbBr 3 films using room temperature CL.…”
Section: Ch(nh 2 ) 2 Pbbr 3 (Influence Of Solvent)mentioning
confidence: 99%